Identifying the attributes of successful small apparel businesses in Armenia - Khachatryan, Lilit (Kansas State University, 2019)
Because finding a job in the apparel and textile sector can be a challenging task for the graduates of the apparel and textile programs in Armenia, the focus of this study is to find the attributes of successful small apparel businesses in Armenia and to identify the knowledge and skills graduates need to secure a job, to succeed at it, and potentially open their own small apparel business. Specifically, the purpose of this study is to: 1) identifying the factors leading to the success of small apparel businesses in Armenia; 2) learn what obstacles hinder the success of small apparel businesses in Armenia; 3) gain understanding of how the small apparel businesses in Armenia address the needs and wants of their customers; and 4) establish what type of professional development would contribute to the success of the small businesses. The study also: 1) explores what knowledge and skills successful apparel businesses in Armenia are looking for in new employees; and 2) provides recommendations for curriculum changes at Armenian apparel and textile programs which would help the graduates of Apparel and Textile programs in finding a job in the apparel and textile industry or in starting their own businesses. This study adopted a qualitative approach and collected data through semi-structured interviews with 11 Armenian small apparel business owners. According to the owners of small apparel businesses in Armenia who participated in this study, one of the most important factors contributing to the success of small firms is effective utilization of innovative marketing techniques. At the same time, the use of innovative marketing techniques is still at its infancy in the small apparel business in Armenia, while the graduates of apparel and textile programs in that country to not receive marketing or business education. Other factors discussed by the participants as contributing to the success of small firms are professional and personal characteristics of the business owners, quality employees, and good customer service. Based on these responses, curriculum recommendations are provided for the apparel and textile programs in Armenia that reflect the knowledge and skills the graduates need to: 1) be successful at finding a job in the apparel and textiles industry and at excelling at it; and 2) opening and operating their own small apparel businesses. The findings of this study can be useful for graduates of the Armenian apparel and textile programs because they can learn what type of knowledge and skills are needed to succeed in the garment and textile sector in Armenia. Additionally, the apparel and textile programs in Armenia may use the results of this study to modify their curriculum, and include courses in marketing, business, and consumer behavior/service, to better equip their students with tools which will contribute to their professional success. Finally, the small businesses may use the findings to better understand how to succeed by adapting various marketing techniques, how to attract quality employees, and how to better address the needs and wants of their customers.
Keywords: Apparel; Successful businesses; Armenia; Marketing; Small business; Textile programs